1. The problem statement, all variables and given/known data Find (use shortcut): x(t) = 2e-4tu(t) * e2tu(t) * t2σ(t - 2) 2. Relevant equations Convolution properties: # "shape of Y (output) is different from x1, x2" # x1 * x2 = x2 * x1 # x1 * (x2 + x3) = (x1 * x2) + (x1 * x3) # x1(t) = * x2(t) * x3(t) * ..... # step * ramp = parabolic function # eatu(t) * ebtu(t) = (1/a-b)[eat - ebt]u(t) 3. The attempt at a solution 2e-4tu(t) * e2tu(t) * t2σ(t - 2) just doing 2e-4tu(t) * e2tu(t) for now, and using the last property listed: = 2(1/(2+4))[e-4t - e2t]u(t) = (1/3)[e-4t - e2t]u(t) I am unsure how to go about doing convolution with the * t2σ(t - 2) at this point, please help. Thanks!